Method for reinforcing copper-based composite material based on MAX phase

Through wet dispersion and ball milling technology, combined with high-temperature reduction and discharge plasma sintering technology, Cu-Ti4AlN3 composite material was prepared, which solved the problem of insufficient mechanical properties of the existing MAX phase reinforced copper matrix, and achieved the improvement of the mechanical properties and the maintenance of the material.

CN119753409AActive Publication Date: 2025-04-04HEFEI UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411957363.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-04
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing preparation methods for MAX phase reinforced copper matrix have problems such as low interface bonding strength, insufficient material density and large grain growth of copper matrix, resulting in insufficient mechanical properties.

Method used

Wet dispersion, ball milling, drying, reducing and discharge plasma sintering processes are adopted to form Cu-Ti4AlN3 composite material through the mixing and ball milling of Ti4AlN3 powder and high-purity Cu powder to improve the mechanical properties of the material.

Benefits of technology

It significantly improves the mechanical properties of Cu-Ti4AlN3 composite materials, maintains excellent conductivity, and provides the possibility for large-scale production of high-performance electrical contact materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for reinforcing a copper-based composite material based on an MAX phase. The method comprises the following steps: (1) powder pretreatment; (2) high-temperature reduction; and (3) spark plasma sintering. The MAX phase Ti4AlN3 is added, so that the mechanical property of the copper-based alloy is enhanced due to the properties of high elastic modulus, good high-temperature plasticity, good thermal shock resistance and the like of the MAX phase Ti4AlN3; during traditional ball milling, a large amount of heat is easily generated in the process, copper powder is agglomerated due to the fact that copper is soft, and the obtained powder is large in particle size, powder is replaced with suspension liquid, the heat generated by ball milling is transmitted by adding ethyl alcohol, air is isolated, sodium dodecyl benzoate is used as a dispersing agent, and the powder is prepared. The capability of powder aggregation is reduced, and the ball milling process is accelerated; and the grain size of the alloy is refined through the combined action of plasma activation and sintering densification, and finally the compact Cu-Ti4AlN3 composite material with excellent mechanical properties and wider application is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper-based tensile materials, and in particular relates to a method for reinforcing a copper-based composite material based on a MAX phase. Background Art

[0002] Copper-based alloys are widely used in various electronic components due to their excellent electrical properties, but their poor mechanical properties limit their application in many emerging fields. In order to meet the high-performance requirements brought about by the progress of the times, the comprehensive mechanical properties of copper alloys need to be further improved.

[0003] MAX phase is a new type of ternary layered ceramic material with the chemical formula M n + 1 AX n ,n = 1, 2, 3, MAX phase material combines the advantages of metal and ceramic, with good thermal conductivity, electrical conductivity and thermal shock resistance. It can maintain plasticity at high temperatures and can be processed like metal and graphite. In addition, it also has high yield strength, high melting point, high thermal stability and excellent oxidation resistance and corrosion resistance. Ti4AlN3 has a series of excellent properties of MAX phase, such as high elastic modulus, good high temperature plasticity and thermal shock resistance, so it is a good method to use Ti4AlN3 to strengthen the copper matrix.

[0004] Currently, the commonly used preparation methods for MAX phase-reinforced copper matrix mainly include powder metallurgy, spark plasma sintering, hot pressing sintering, etc., but there are some problems, such as: the wettability between the MAX phase and the copper matrix is ​​poor, resulting in low bonding strength at the interface, and cracks are easily generated at the interface when subjected to force; as well as insufficient material density, increased porosity, or grain growth of the copper matrix. Summary of the invention

[0005] The purpose of the present invention is to provide a method for reinforcing a copper-based composite material based on a MAX phase, so that the mechanical properties of the prepared Cu-Ti4AlN3 composite material are significantly improved.

[0006] To achieve the above objectives, the present invention uses the following technical solutions: A method for reinforcing a copper-based composite material based on a MAX phase, specifically comprising the following steps: (1) Powder pretreatment Weigh high-purity Cu powder and Ti4AlN3 powder respectively and add them to a beaker in turn, add anhydrous ethanol until the powder is completely submerged, then add a dispersant, place the beaker in a magnetic stirrer for heating and stirring, stir thoroughly and add anhydrous ethanol again until the powder is submerged, put the slurry into a ball mill, add carbide balls, and after assembly, fix the ball mill in a planetary ball mill for ball milling; (2) High temperature reduction The slurry after ball milling in step (1) is taken out and placed in a beaker, and the beaker is placed in a drying oven for drying. The dried powder is ground evenly and spread on a ceramic firing boat and then placed in a tube furnace. After setting the program, it is reduced in a hydrogen atmosphere to finally obtain a Cu-Ti4AlN3 composite powder; (3) Spark plasma sintering The reduced Cu-Ti4AlN3 composite powder in step (2) is ground and added into a graphite mold, and the graphite mold is placed in a furnace chamber of a spark plasma sintering furnace for pre-compaction. After setting the program, the furnace chamber is vacuum treated, and then sintering is performed. After sintering, a Cu-Ti4AlN3 composite material is obtained.

[0007] In the step (1), the mass fraction of Ti4AlN3 powder is 0.5-1.0%, and the rest is high-purity Cu powder. The Cu powder is high-purity electrolytic Cu powder, in the shape of grape bunches, with a purity of 99.999% and a particle size of 1-3 μm. The purity of Ti4AlN3 powder is 98%, and the particle size is 700-800 mesh.

[0008] The magnetic stirrer in step (1) is a DF-101S heat-collecting magnetic stirrer, the stirring temperature is 25-35° C., the stirring time is set to 6-8 h, and in addition to an appropriate amount of anhydrous ethanol, sodium dodecylbenzoate is added to the beaker as a dispersant, the amount of which is determined according to the dispersion of the mixed powder to promote more uniform dispersion of the powder.

[0009] The planetary ball mill in step (1) is a QM-QX4 omnidirectional planetary ball mill produced by Nanjing University of Science and Technology, the ball milling speed (rotation speed) is 600 rpm, the ball-to-material ratio is 5:1, the ball milling time is 4 h, and the ball tank and the ball milling medium are both made of cemented carbide.

[0010] The slurry after ball milling in step (2) is taken out and placed in a beaker, and anhydrous ethanol is used to repeatedly rinse the residual slurry on the wall of the ball mill and the surface of the alloy balls in the beaker, and then placed in a drying oven for drying. The model of the drying oven is DHG-9000-9005, the drying temperature is 50-60°C, and the drying time is 12 h.

[0011] The high temperature tube furnace model in step (2) is GSL-1200X, and the setting program is as follows: heating from room temperature to 600°C at 10°C / min, keeping the temperature for 2 h, then decreasing the temperature to 500°C at 10°C / min, and then cooling to room temperature with the furnace.

[0012] The gas introduced in step (2) is 10% H2-90% Ar, and the introduction amount is 300-350 ml / min.

[0013] In the step (3), the inner diameter of the graphite mold is 20 mm, the outer diameter is 60 mm, and the height is 70 mm. Carbon paper is used to isolate the Cu-Ti4AlN3 composite powder from the graphite mold to facilitate sampling and demoulding after sintering.

[0014] In the step (3), the spark plasma sintering furnace model is LaboxTM-300, and a thermocouple is used for temperature measurement, and the front end of the thermocouple is inserted into the temperature measurement hole of the graphite mold.

[0015] The spark plasma sintering setting program in the step (3) is as follows: the temperature is raised from room temperature to 550-600°C and kept at this temperature for 5 minutes, then the temperature is further raised to 850-900°C and kept at this temperature for 5 minutes, the heating rate is 80-100°C / min, the pre-compression pressure is 10 MPa, the pressure is raised to 50 MPa during the second heating process, and the temperature is kept at this temperature for 5 minutes before cooling with the furnace.

[0016] The innovation of the present invention lies in: In terms of material design: by mixing Cu powder and Ti4AlN3 powder in a certain proportion, the high elastic modulus, good high temperature plasticity and thermal shock resistance of Ti4AlN3 are fully utilized to achieve the reinforcement effect on the copper matrix.

[0017] Preparation method: The preparation method of the present invention is composed of wet dispersion, ball milling, drying, reduction and spark plasma sintering processes, so that the material has a specific crystal structure and phase composition, thereby improving the performance of the material. This preparation method provides the possibility for large-scale production of this high-performance electrical contact material.

[0018] Performance optimization: By reinforcing the copper-based composite material with Ti4AlN3, the mechanical properties of the copper-based alloy are further improved, and the excellent conductivity is maintained, showing excellent overall performance.

[0019] Compared with the existing process technology, the present invention has at least the following beneficial effects: The present invention adds MAX phase Ti4AlN3, which has high elastic modulus, good high-temperature plasticity and thermal shock resistance, etc., to enhance the mechanical properties of the copper-based alloy; in traditional ball milling, a large amount of heat is easily generated in the process, and copper powder agglomerates due to its soft texture, so that the obtained powder particle size is larger; the present invention replaces the powder with a suspension, transfers the heat generated by ball milling by adding ethanol, isolates the air, and uses sodium dodecylbenzoate as a dispersant, which reduces the ability of the powder to aggregate into agglomerates and accelerates the ball milling process; the spark plasma sintering technology refines the grain size of the alloy through the combined action of plasma activation and sintering densification, and finally prepares a dense Cu-Ti4AlN3 composite material with superior mechanical properties and wider application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the surface morphology of the raw material high-purity copper powder; Figure 2 This is a high-magnification fracture morphology of the Cu-1.0%Ti4AlN3 composite material; Figure 3 This is a high-magnification fracture morphology of the Cu-0.5%Ti4AlN3 composite material; Figure 4 This is the EDS analysis diagram of Cu-1.0%Ti4AlN3 composite material; Figure 5 This is the EDS analysis diagram of Cu-0.5%Ti4AlN3 composite material. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0022] Example 1 The Cu-Ti4AlN3 composite material in this embodiment is processed by wet dispersion, ball milling, drying, reduction and spark plasma sintering processes, wherein the mass fraction of Ti4AlN3 is 1.0%, and the rest is high-purity electrolytic Cu powder in the shape of grape clusters with a purity of 99.999% and a particle size of 1-3μm. The purity of Ti4AlN3 powder is 98% and the particle size is 700-800 mesh.

[0023] The preparation method of the Cu-Ti4AlN3 composite material in this embodiment is as follows: (1) Powder pretreatment Weigh 49.5g high-purity Cu powder and 0.5g Ti4AlN3 powder respectively, add them to a beaker, add anhydrous ethanol until the powder is completely submerged, then add 0.06g sodium dodecylbenzoate, place the beaker in a magnetic stirrer, stir at 25-35 °C for 6-8h, stir thoroughly and add anhydrous ethanol again until the powder is submerged; put the slurry into a ball mill, add cemented carbide balls at a ball-to-material ratio of 5:1, and after assembly, fix the ball mill in a planetary ball mill for 4h; (2) High temperature reduction The slurry after ball milling is taken out and placed in a beaker, and the residual slurry on the wall of the ball mill and the surface of the alloy ball is repeatedly washed with anhydrous ethanol in the beaker, and then the beaker is placed in a drying oven for drying. The drying temperature is 50-60 ° C, and the drying time is 12 h. After drying, the obtained powder is ground and evenly spread on a ceramic firing boat and then placed in a tube furnace. A 10% H2-90% Ar gas is introduced at a flow rate of 300-350 ml / min to produce a reducing atmosphere. The program is set to increase the temperature from room temperature to 600 ° C at 10 ° C / min, and then decrease to 500 ° C at 10 ° C / min after keeping the temperature for 2 h, and then cool to room temperature with the furnace to finally obtain Cu-Ti4AlN3 composite powder; (3) Spark plasma sintering The reduced Cu-Ti4AlN3 composite powder is ground and added into a graphite mold wrapped with carbon paper (the inner diameter of the graphite mold is 20 mm, the outer diameter is 60 mm, and the height is 70 mm. The Cu-Ti4AlN3 composite powder and the graphite mold are isolated by carbon paper to facilitate sampling and demolding after sintering). The graphite mold is placed in the furnace chamber of a spark plasma sintering furnace and pre-compacted at a pressure of 10 MPa. The front end of the thermocouple is inserted into the temperature measuring hole of the graphite mold. The furnace chamber door is closed for vacuum treatment. After the furnace chamber reaches the vacuum level, sintering is performed according to the set program. The program is as follows: from room temperature to 550-600 ℃, and the temperature is kept for 5 min, and then the temperature is continued to be increased to 850-900 ℃, and the temperature is kept for 5 min. The heating rate is 80-100 ℃ / min. During this process, the pressure is increased to 50 MPa. After the temperature is kept for 5 min, the Cu-Ti4AlN3 composite material is obtained by cooling with the furnace.

[0024] Example 2 The Cu-Ti4AlN3 composite material in this embodiment is processed by wet dispersion, ball milling, drying, reduction and spark plasma sintering processes, wherein the mass fraction of Ti4AlN3 is 1.0%, and the rest is high-purity electrolytic Cu powder in the shape of grape clusters with a purity of 99.999% and a particle size of 1-3μm. The purity of Ti4AlN3 powder is 98% and the particle size is 700-800 mesh.

[0025] The preparation method of the Cu-Ti4AlN3 composite material in this embodiment is as follows: (1) Powder pretreatment Weigh 49.75g high-purity Cu powder and 0.25g Ti4AlN3 powder respectively, add them into a beaker, add anhydrous ethanol until the powder is completely submerged, then add 0.06g sodium dodecylbenzoate, place the beaker in a magnetic stirrer, stir at 25-35 °C for 6-8h, stir thoroughly and add anhydrous ethanol again until the powder is submerged; put the slurry into a ball mill, add cemented carbide balls at a ball-to-material ratio of 5:1, and after assembly, fix the ball mill in a planetary ball mill for 4h; (2) High temperature reduction The slurry after ball milling is taken out and placed in a beaker, and the residual slurry on the wall of the ball mill and the surface of the alloy ball is repeatedly washed with anhydrous ethanol in the beaker, and then the beaker is placed in a drying oven for drying. The drying temperature is 50-60 ° C, and the drying time is 12 h. After drying, the obtained powder is ground and evenly spread on a ceramic firing boat and then placed in a tube furnace. A reducing atmosphere is produced by passing 10% H2-90% Ar gas at a flow rate of 300-350 ml / min. The program is set to increase the temperature from room temperature to 600 ° C at 10 ° C / min, and then decrease the temperature to 500 ° C at 10 ° C / min after keeping the temperature for 2 h, and then cool to room temperature with the furnace to finally obtain Cu-Ti4AlN3 composite powder; (3) Spark plasma sintering The reduced Cu-Ti4AlN3 composite powder is ground and added into a graphite mold wrapped with carbon paper (the inner diameter of the graphite mold is 20 mm, the outer diameter is 60 mm, and the height is 70 mm. The Cu-Ti4AlN3 composite powder and the graphite mold are isolated by carbon paper to facilitate sampling and demolding after sintering). The graphite mold is placed in the furnace chamber of a spark plasma sintering furnace and pre-compacted at a pressure of 10 MPa. The front end of the thermocouple is inserted into the temperature measuring hole of the graphite mold. The furnace chamber door is closed for vacuum treatment. After the furnace chamber reaches the vacuum level, sintering is performed according to the set program. The program is as follows: from room temperature to 550-600 ℃, and the temperature is kept for 5 min, and then the temperature is continued to be increased to 850-900 ℃, and the temperature is kept for 5 min. The heating rate is 80-100 ℃ / min. During this process, the pressure is increased to 50 MPa. After the temperature is kept for 5 min, the Cu-Ti4AlN3 composite material is obtained by cooling with the furnace.

[0026] Table 1 below is Cu, Cu-1.0%Ti4AlN 3, Table of mechanical properties of Cu-0.5%Ti4AlN3. Made by spark plasma sintering, its tensile strength and hardness are significantly improved compared with pure copper.

[0027] Table 1 Performance table of sample blocks from Figure 1It can be seen that the copper powder is spherical with a particle size of 1-3 μm, the powder is agglomerated into a grape bunch shape, and the surface of the copper powder is smooth.

[0028] from Figure 2 , Figure 3 It can be seen that the ports of Cu-1.0%Ti4AlN3 and Cu-0.5%Ti4AlN3 present an overall morphology of equiaxed dimple aggregation and the distribution of dimples is relatively uniform; at the same time, tear edges and some steps are found in the fracture, which is considered to be a mixed fracture dominated by ductile fracture.

[0029] from Figure 4 , Figure 5 It can be seen that various element additions can be found from the energy spectrum analysis.

[0030] The present invention adds MAX phase Ti4AlN3, introduces its high elastic modulus, good high-temperature plasticity and other properties, strengthens the copper-based composite material, and improves the mechanical properties of the copper alloy; during traditional ball milling, a large amount of heat is easily generated in the process, and because copper is relatively soft, copper powder agglomerates, making the obtained powder particle size larger; the present invention replaces powder with a suspension, transfers the heat generated by ball milling by adding ethanol, isolates the air, and uses sodium dodecylbenzoate as a dispersant, which reduces the ability of powder to aggregate into agglomerates and accelerates the ball milling process; the spark plasma sintering technology refines the grain size of the alloy through the combined action of plasma activation and sintering densification, and finally prepares a dense Cu-Ti4AlN3 composite material with superior mechanical properties and wider application.

[0031] The above embodiments only illustrate specific implementations of the present disclosure, but the implementations of the present disclosure are not limited by the above contents. Any changes, modifications, substitutions, combinations, and simplifications made without substantially departing from the main idea and principle of the inventive concept of the present disclosure shall be equivalent replacement methods and shall be included in the scope of protection determined by the claims.

Claims

1. A method for reinforcing a copper-based composite material based on a MAX phase, characterized in that: The specific steps include: (1) Powder pretreatment Weigh high-purity Cu powder and Ti4AlN3 powder respectively and add them to a beaker in turn, add anhydrous ethanol until the powder is completely submerged, then add a dispersant, place the beaker in a magnetic stirrer for heating and stirring, stir thoroughly and add anhydrous ethanol again until the powder is submerged, put the slurry into a ball mill, add carbide balls, and after assembly, fix the ball mill in a planetary ball mill for ball milling; (2) High temperature reduction The slurry after ball milling in step (1) is taken out and placed in a beaker, and the beaker is placed in a drying oven for drying. The dried powder is ground evenly and spread on a ceramic firing boat and then placed in a tube furnace. After setting the program, it is reduced in a hydrogen atmosphere to finally obtain a Cu-Ti4AlN3 composite powder; (3) Spark plasma sintering The reduced Cu-Ti4AlN3 composite powder in step (2) is ground and added into a graphite mold, and the graphite mold is placed in a furnace chamber of a spark plasma sintering furnace for pre-compaction. After setting the program, the furnace chamber is vacuum treated, and then sintering is performed. After sintering, a Cu-Ti4AlN3 composite material is obtained.

2. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: In the step (1), the mass fraction of Ti4AlN3 powder is 0.5-1.0%, and the rest is high-purity Cu powder. The Cu powder is high-purity electrolytic Cu powder, in the shape of grape bunches, with a purity of 99.999% and a particle size of 1-3 μm. The purity of Ti4AlN3 powder is 98%, and the particle size is 700-800 mesh.

3. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: The magnetic stirrer in step (1) is a DF-101S heat-collecting magnetic stirrer, the stirring temperature is 25-35°C, the stirring time is set to 6-8 h, and in addition to an appropriate amount of anhydrous ethanol, sodium dodecylbenzoate is added to the beaker as a dispersant, the amount of which is determined according to the dispersion of the mixed powder to promote more uniform dispersion of the powder.

4. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: The planetary ball mill in step (1) is a QM-QX4 omnidirectional planetary ball mill manufactured by Nanjing University of Science and Technology, the ball milling speed is 600 rpm, the ball-to-material ratio is 5:1, the ball milling time is 4 h, and the ball tank and the ball milling medium are both made of cemented carbide.

5. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: The slurry after ball milling in step (2) is taken out and placed in a beaker, and anhydrous ethanol is used to repeatedly rinse the residual slurry on the wall of the ball mill and the surface of the alloy balls in the beaker, and then placed in a drying oven for drying. The model of the drying oven is DHG-9000-9005, the drying temperature is 50-60°C, and the drying time is 12 h.

6. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: The model of the tube furnace in step (2) is GSL-1200X, and the setting program is as follows: heating from room temperature to 600°C at 10°C / min, keeping the temperature for 2 h, then decreasing the temperature to 500°C at 10°C / min, and then cooling to room temperature with the furnace.

7. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: The gas introduced in step (2) is 10% H2-90% Ar, and the introduction amount is 300-350 ml / min.

8. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: In the step (3), the inner diameter of the graphite mold is 20 mm, the outer diameter is 60 mm, and the height is 70 mm. Carbon paper is used to isolate the Cu-Ti4AlN3 composite powder from the graphite mold to facilitate sampling and demoulding after sintering.

9. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: In the step (3), the spark plasma sintering furnace model is LaboxTM-300, and a thermocouple is used for temperature measurement, and the front end of the thermocouple is inserted into the temperature measurement hole of the graphite mold.

10. A method for reinforcing a copper-based composite material based on a MAX phase as claimed in claim 1, characterized in that: The spark plasma sintering setting program in the step (3) is as follows: the temperature is raised from room temperature to 550-600 ° C and kept at this temperature for 5 min, then the temperature is further raised to 850-900 ° C and kept at this temperature for 5 min, the heating rate is 80-100 ° C / min, the pre-compression pressure is 10 MPa, the pressure is raised to 50 MPa during the second heating process, and the temperature is kept at this temperature for 5 min before cooling with the furnace.

Citation Information

Patent Citations

  • Preparation method of layered ternary ceramic reinforced copper composite material

    CN102242302A

  • Method for preparing Cu-TiB2-Zr through composite dispersion treatment suspension ball milling method

    CN117845085A

  • Preparation method for enhancing wear resistance of copper-carbon composite material through Ti2AlC

    CN119351814A

  • Syntactic metal matrix materials and methods

    US20130098203A1

  • Max phase material, preparation method therefor and application thereof

    US20200407281A1